Charting The Multichannel Future: Retail Choices And Constraints - Reynolds, J (Emerald Group Publishing Ltd., 2002)

(untitled)
Whilst the events of 2000 and 2001 would appear to have reduced significantly the attractiveness of e-commerce as a viable source of revenue growth for retailers, writing off electronic distribution channels may be premature. Growth in online transactions in, for example, the USA and the UK -whilst slower than commentators had predicted - is nevertheless encouraging. Retailing appears to be polarizing between those willing to embrace e-commerce for longer-term benefit and those for whom e-commerce is not seen as a desirable route to growth. The indirect, informational effect of the Internet on the consumer buying process and the perception of retail brands is a further consideration for those contemplating multi-channel futures. Finally, the article illustrates that the integrative challenges of multi-channel retailing are capable of being resolved in more than one way.